Pengaruh Penambahan Serat Ijuk Terhadap Kuat Tekan Beton - Tenardhy Aryarama Wijaya; Dewi Bussaina Ghassani; Alvino (JERA : Journal of Engineering Research and Application, 2024)
The rapid development of the population and also the development of technology has encouraged the birth of several new technologies specifically for the field of civil engineering, infrastructure and buildings. One of the various building materials that we often encounter is concrete. Concrete is a material composed of several mixtures consisting of: sand or fine aggregate, gravel or coarse aggregate, cement, water as an ingredient to bind all the ingredients that make up concrete. In this study the authors took the title effect of adding palm fiber to the compressive strength of concrete. The purpose of this research is to determine the compressive strength of normal concrete and concrete after adding palm fiber. The method used is research on making concrete and then adding palm fiber at 2% of the cement weight with a number of test objects of 9. From the test results, the average compressive strength of normal concrete is 17 MPa and for fiber concrete the average compressive strength has increased. to 19 MPa, and the ratio between normal concrete and palm fiber concrete is 1.12.